SOCIAL PERFORMANCE THEORIES & DEFINITION: A SYSTEMATIC LITERATURE REVIEW - Layman, Chrisanty V.; Sasmoko; Budiastuti, Dyah; Sanny, Lim (International Journal of Psychosocial Rehabilitation, 2020)
Along with increasing challenges and complex social world problems is the rise of conscience and social values for firms, along with the expectation of better accountability of their actions to both shareholders and various stakeholders. Social performance emerges as the cultivation of social identity within firms while competing with its available resources. However, conceptualization of social performance remains providential and there are still controversies regarding its definition, theories, and application. This study reviews social performance literature and identifies the gaps and trends related to building social performance measures for firms. The aim of the study is to identify various definition, disparities and gaps in literature on work of social performance and to provide a conceptual synthesis for possible application of social performance in firms. A systematic approach is adopted, identifying relevant articles related to social performance between 2015 - 2019 published in Scopus peer-reviewed journals. Findings describes social performance existing definitions, trends, possible measures, and application. The novelty of the paper is in the comprehensive search and systematic review of most recent social performance studies contributing to future research directions for social performance in the various industry application.